AP or GP?

Algebra Level 3

In a set of four numbers, the first three are in a Geometric Progression and the last three are in an Arithmetic Progression with a common difference of 6. If the first number is same as the fourth, what is the sum of the four numbers?


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Discussions for this problem are now closed

Nihar Mahajan
Dec 26, 2014

As B , C , D form an A.P with common difference as 6 ,

B=B , C = B+6 , D = B+12

Also , A = D = B+12

As A , B , C form a G.P ,

B/A = C/B ...............[ Common Ratio ]

B^2 = A * C

B^2 = (B + 12) * (B + 6)

B^2 = B^2 + 18B + 72

18B = -72

B = -4

C = -4 + 6 = 2

A = D = -4 +12 = 8

So , A + B + C + D = 8 - 4 + 2 + 8 = 14 :)

Pranjal Jain
Dec 12, 2014

Let first term be a a , common ratio be r r .

Since first 3 terms are in GP, second term is a r ar and third would be a r 2 ar^{2} .

Now, we are given that last 3 are in AP, so a r 2 a r = 6 ar^{2}-ar=6 and a r + 12 = a ar+12=a [ 4 t h t e r m = 1 s t t e r m ] [4^{th} term=1^{st} term]

a r + 12 = a ar+12=a r = a 12 a \Rightarrow r=\dfrac{a-12}{a}

a r 2 a r = 6 ar^{2}-ar=6 a × ( a 12 a ) 2 ( a 12 ) = 6 \Rightarrow a×\Big (\dfrac{a-12}{a}\Big )^2-(a-12)=6 ( a 12 ) 2 = a ( a 6 ) \Rightarrow (a-12)^{2}=a(a-6)

Solving this linear equation gives a = 8 a=8 .

a r + 12 = a ar+12=a r = 1 2 \Rightarrow r=-\dfrac{1}{2}

So the sequence is 8,-4,2,8 \color{#D61F06}{\text{8,-4,2,8}} which adds up to give 14 \color{#3D99F6}{\boxed{14}}

Steven Yuan
Dec 12, 2014

Let A , B , C , A A, B, C, A be our desired sequence, where A , B , A, B, and C C are real numbers. Since A , B , C A, B, C is a geometric sequence, we have B = A C . B = \sqrt{AC}. Since B , C , A B, C, A is an arithmetic sequence, we have C = B + A 2 . C = \dfrac{B+A}{2}. Substituting this value of C C into our first equation, we get

B = A ( B + A 2 ) 2 B = 2 A ( B + A ) 4 B 2 = 2 A B + 2 A 2 A 2 + A B 2 B 2 = 0 ( A + 2 B ) ( A B ) = 0 A = 2 B or B . \begin{aligned} B &= \sqrt{A\left(\frac{B+A}{2}\right)} \\ 2B &= \sqrt{2A(B+A)} \\ 4B^{2} &= 2AB + 2A^{2} \\ A^{2} + AB - 2B^{2} &= 0\\ (A + 2B)(A - B) &= 0\\ A &= -2B \quad \text{or} \quad B. \\ \end{aligned}

We discard A = B A = B , since that does not satisfy the common difference of 6 6 criteria, so A = 2 B , A = -2B, and our sequence becomes 2 B , B , 1 2 B , 2 B . -2B, B, -\dfrac{1}{2}B, -2B.

Finally, we solve B + 6 = 1 2 B , B + 6 = -\dfrac{1}{2}B, which yields B = 4. B = -4. Thus, our sequence is 8 , 4 , 2 , 8 , 8, -4, 2, 8, which indeed satisfy the criteria given in the problem. The sum is 14 . \boxed{14}.

Christian Daang
Jan 3, 2015

Let the Arithmetic Progression be D-12, D-6 and D

Since the 1st number = 4th number, then, the numbers is: D, D-12, D-6, D with a sum of 4D-18

by using the ratio of a geometric progression,

(D-12)/D = (D-6)/(D-12)

D^2 - 6D = D^2 - 24D + 144

18D = 144 ---> 4D = 32

Therefore, the sum of the 4 numbers is 4D - 18 = 32 - 18 = 14 (ans)..

Francois Tardieu
Jan 2, 2015

we have : A A , B = q A B=qA , C = q 2 A = q A + 6 C=q^2A=qA+6 and D = A = q A + 12 D=A=qA+12 . From last equality, A ( 1 q ) = 12 A(1-q)=12 . From third equality, q A ( q 1 ) = 6 qA(q-1)=6 so with the precedent we get, 12 q = 6 -12q=6 , hence, q = 1 2 q =-\dfrac{1}{2} . Replace q q in last we get, A = 2 × 12 3 = 8 A=\dfrac{2 \times 12}{3}=8 then, A + B + C + D = 14 A+B+C+D=14

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...